ANALISIS KELAYAKAN MINYAK TRANSFORMATOR DIDASARKAN PADA PARAMETER STANDAR MINYAK ISOLASI PADA TRANSFORMATOR DAYA 60 MVA DI GARDU INDUK KILIRAN JAO - Fikri, Al Hadi; Dhofir, Moch.; Utomo, Teguh (Jurnal Mahasiswa TEUB, 2024)
Testing and analyzing the condition of power transformer oil is very important to ensure the reliability and optimal performance of the transformer during operation. This research was conducted on the 60 MVA unit 2 power transformer at Kiliran Jao Substation with a focus on testing transformer oil characteristics and dissolved gas analysis (DGA). This transformer has a strategic role in electrical power distribution, where transformer oil is used as an insulating and cooling medium to support optimal device performance. This research consists of several stages. The first stage is a literature study, which is carried out by collecting theories through relevant articles, journals, and previous research to support the research discussion. The second stage is field observation, which is carried out at PT PLN (Persero) UPT Padang to learn how to take oil samples and the parameters tested. The transformer studied was a 60 MVA 150 kV power transformer unit 2 with serial number 3011170055. Furthermore, primary and secondary data were collected. Primary data includes transformer specifications and field test results, while secondary data includes historical data of previous test results. These data are then processed to analyze the physical and chemical condition of the transformer oil and detect dissolved gases that indicate potential internal faults. The data obtained was evaluated by comparing it against the IEEE 2008 standard to determine the operational feasibility of the transformer oil. The DGA test results show that the total combustible gas concentration (TDCG) is at Condition 1, which means the transformer oil is still safe for normal operation. However, there are indications of ethane gas (C₂H₆) in Condition 4, with concentrations exceeding the threshold indicating potential overheating in the temperature range of 300°C to 500°C. Testing the characteristics of transformer oil shows that parameters such as breakdown voltage, moisture content, acid content, viscosity, color, sediment, flash point, and interface tension are in good condition according to applicable standards. In conclusion, although the transformer oil is still suitable for use, intensive monitoring is needed of certain parameters, especially ethane gas, to anticipate the potential for overheating that can interfere with transformer reliability. Routine maintenance and advanced analysis are needed to maintain oil quality and prevent transformer damage, so that the operational sustainability of the power distribution system can be guaranteed. This research emphasizes the importance of periodic testing as a preventive measure to improve electrical system reliability.Keywoards: Analysis, Dissolved Gas Analysis, Characteristics, Nynas Nitro Lybra oil